2015
DOI: 10.1128/iai.03015-14
|View full text |Cite
|
Sign up to set email alerts
|

Role of Copper Efflux in Pneumococcal Pathogenesis and Resistance to Macrophage-Mediated Immune Clearance

Abstract: In bacteria, the intracellular levels of metals are mediated by tightly controlled acquisition and efflux systems. This is particularly true of copper, a trace element that is universally toxic in excess. During infection, the toxic properties of copper are exploited by the mammalian host to facilitate bacterial clearance. To better understand the role of copper during infection, we characterized the contribution of the cop operon to copper homeostasis and virulence in Streptococcus pneumoniae. Deletion of eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
88
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 51 publications
2
88
1
Order By: Relevance
“…While our work demonstrates urinary Cu mobilization via ceruloplasmin during UTI with Gram-negative pathogens, whether the Cu mobilization response is conserved during UTI with Gram-positive pathogens remains to be examined. Mutants lacking Cu detoxification systems in diverse pathogens, including Cryptococcus neoformans (a fungus), K. pneumoniae, Mycobacterium tuberculosis, Salmonella enterica serovar Typhimurium, Streptococcus pneumoniae, and UPEC, are attenuated in animal models of infection (11,(26)(27)(28)(29)(30)(31). Our results presented here elucidate the protective role of Cu in the pathogenesis of UTI.…”
Section: Discussionmentioning
confidence: 65%
“…While our work demonstrates urinary Cu mobilization via ceruloplasmin during UTI with Gram-negative pathogens, whether the Cu mobilization response is conserved during UTI with Gram-positive pathogens remains to be examined. Mutants lacking Cu detoxification systems in diverse pathogens, including Cryptococcus neoformans (a fungus), K. pneumoniae, Mycobacterium tuberculosis, Salmonella enterica serovar Typhimurium, Streptococcus pneumoniae, and UPEC, are attenuated in animal models of infection (11,(26)(27)(28)(29)(30)(31). Our results presented here elucidate the protective role of Cu in the pathogenesis of UTI.…”
Section: Discussionmentioning
confidence: 65%
“…S. pyogenes also shared sequence identity with S. pneumoniae cop operon-encoded proteins (38% identity to CopY and 44% to CopA) but lacked CupA. CupA, which plays a role in copper resistance in S. pneumoniae (13,22), has 33% identity to a hypothetical protein, Spy_0115, of unknown function in S. pyogenes MGAS5005.…”
Section: S Pyogenes Clinical Isolates Contain a Cop Operon-like Locusmentioning
confidence: 99%
“…In each of these organisms, the cop operon encodes a copper-transporting CPx-type ATPase (CopA/CopB), a copper-responsive repressor that represses the operon under conditions of low copper concentrations (CopY/CopR), and a copper chaperone that shuttles copper intracellularly (CopZ) (8,(13)(14)(15)(16)(17). Animal studies have demonstrated that deletion of a coppertransporting ATPase results in decreased survival of Mycobacterium tuberculosis (18), Pseudomonas aeruginosa (19), Listeria monocytogenes (20), Salmonella enterica serovar Typhimurium (21), and S. pneumoniae (13,22).…”
mentioning
confidence: 99%
“…In the case of Fe(II), one aspect of the bacterial peroxide stress response involves the decreased expression of Fe uptake systems and the increased expression of Fe storage proteins that effectively sequester Fe and thus prevent prooxidant activity (12)(13)(14). In contrast, copper concentrations within the bacterial cell are held very low as a consequence of the action of a Cu efflux system (CopYAZ) that is controlled by a Cu-sensing regulator (CopY) (15)(16)(17). The possibility that Fe ions might also be effluxed from the bacterial cell during peroxide stress has not been widely investigated.…”
mentioning
confidence: 99%